Novel reassortant of H1N1 swine influenza virus detected in pig population in Russia - Ivan Sobolev; Olga Kurskaya; Sergey Leonov; Marsel Kabilov; Tatyana Alikina; Alexander Alekseev; Yuriy Yushkov; Takehiko Saito; Yuko Uchida; Junki Mine; Alexander Shestopalov; Kirill Sharshov (Emerging Microbes and Infections)
Pigs play an important role in interspecies transmission of the influenza virus, particularly as “mixing vessels” for reassortment. Two influenza A/H1N1 virus strains, A/swine/Siberia/1sw/2016 and A/swine/Siberia/4sw/2017, were isolated during a surveillance of pigs from private farms in Russia from 2016 to 2017. There was a 10% identity difference between the HA and NA nucleotide sequences of isolated strains and the most phylogenetically related sequences (human influenza viruses of 1980s). Simultaneously, genome segments encoding internal proteins were found to be phylogenetically related to the A/H1N1pdm09 influenza virus. In addition, two amino acids (129–130) were deleted in the HA of A/swine/Siberia/4sw/2017 compared to that of A/swine/Siberia/1sw/2016 HA.